PEMAHAMAN KONSEP PERKALIAN DENGAN MENGGUNAKAN METODE RME PADA PESERTA DIDIK KELAS III MI MIFTAHUL HUDA - Nina Indriani; Zuha Prisma Salsabila; Alfira Nur Azizah Firdaus (Auladuna: Jurnal Pendidikan Dasar Islam, 2022)
Abstract This study aimed to determine the extent of students' understanding of multiplication arithmetic operations using the RME method. The samples in this study were the 3rd-grade students of MI Miftahul Huda, consisting of 28 students selected using purposive sampling. This study used a quasi-experimental quantitative method with the type of the time-series experiment. The research results indicated that the students’ understanding of multiplication improved. The indicators of multiplication based on the memorization method, multiplication concept with repeated addition, multiplication concept with its properties, and applying the concept of multiplication to story problems showed an increase, therefore it can be concluded that the understanding of the multiplication concepts of the 3rd-grade students of MI Miftahul Huda Jatisari students experienced a significant increase. Students have been able to understand simple mathematical concepts and prove them without always relying upon their memorization results.